2004
DOI: 10.1007/s00436-004-1125-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermiogenesis and the spermatozoon in Taenia crassiceps strobilae WFU strain (Cestoda, Cyclophyllidea, Taeniidae) from golden hamsters

Abstract: Strobilae from Taenia crassiceps (WFU strain) were obtained from outbred hamsters (Mesocricetus auratus) by feeding them viable metacestodes maintained by intraperitoneal passage in female Balb/c mice. Mature and gravid proglottids from strobilae were recovered from hamster intestines and fixed for light and electron microscopy. By light microscopy, the expected structure of taeniid proglottids was observed. Ultrastructural analysis of ten proglottids showed that testicular follicles and vas deferens contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…centripunctata, see Bâ and Marchand 1994b). Similar structures, electron-dense rods, were observed in the dilepidid D. undula (see OEwiderski et al 2000) and in the species of the genus Taenia (see Tian et al 1998, Ndiaye et al 2003a, Willms et al 2004.…”
Section: Spermatozoonsupporting
confidence: 57%
See 1 more Smart Citation
“…centripunctata, see Bâ and Marchand 1994b). Similar structures, electron-dense rods, were observed in the dilepidid D. undula (see OEwiderski et al 2000) and in the species of the genus Taenia (see Tian et al 1998, Ndiaye et al 2003a, Willms et al 2004.…”
Section: Spermatozoonsupporting
confidence: 57%
“…The spermatozoon of A. beema has a single crested body, as it is in the cyclophyllidean families Taeniidae (see Miquel et al 2000, Ndiaye et al 2003a, Willms et al 2004, Mesocestoididae (see Miquel et al 1999), Nematotaeniidae (see Mokhtar-Maamouri and Azzouz-Draoui 1990), Dilepididae (see OEwiderski et al 2000OEwiderski et al , 2002, Dipylidiidae (see , Ndiaye et al 2003b, Miquel et al 2005a and Metadilepididae (see Yoneva et al 2006). Two families, Catenotaeniidae and Davaineidae, are characterised by the presence of two crested bodies on the mature spermatozoon Hidalgo et al 2000;Bâ and Marchand 1994c;Bâ et al 2005a, b).…”
Section: Spermatozoonmentioning
confidence: 99%
“…This is the case of the catenotaeniid Catenotaenia pusilla, the davaineids, the dipylidiids, the metadilepidid Skrjabinoporus merops, the nematotaeniid Nematotaenia chantalae, and the taeniids (Featherston 1971;Mokhtar-Maamouri and Azzouz-Draoui 1990;Bâ and Marchand 1994b;Miquel et al , 2005bMiquel et al , 2009bHidalgo et al 2000;Ndiaye et al 2003a, b;Willms et al 2003Willms et al , 2004Yoneva et al 2006b). In the present study, we demonstrate that T. taeniaeformis also exhibits Type 3 spermiogenesis.…”
Section: Spermiogenesismentioning
confidence: 99%
“…At present, there are ultrastructural studies on spermiogenesis or sperm of the following nine species of the Taeniidae: Echinococcus granulosus, E. multilocularis, Taenia crassiceps, T. hydatigena, T. mustelae, T. parva, T. pisiformis, T. saginata and T. solium (Morseth 1969;Featherston 1971;Barrett and Smyth 1983;Shi et al 1994;Tian et al 1998;Miquel et al 2000;Ndiaye et al 2003a;Willms et al 2003Willms et al , 2004. The purpose of the present paper is to describe the ultrastructure of spermatogenesis of Taenia taeniaeformis with emphasis on the early stages comprising 4 generations of spermatogonia, primary and secondary spermatocytes, spermatids and the entire process of sperm differentiation or spermiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been widely demonstrated that a number of parasites induce apoptosis in their host tissues (Moore and Matlashewshi 1994;Ragland et al 1994;Lopez et al 1995;Toure-Blade et al 1996) Invertebrate tissues of cestoda have very high reproductive capacities (Conn 1993) and are therefore expected to exhibit apoptosis in tissues which are undergoing constant growth and differentiation. The purpose of this paper is to examine the process of PCD in the adult stage of two experimental taeniids, Taenia solium and Taenia crassiceps, grown in the immunosuppressed golden hamster model (Sato and Kamiya 1989;Sato et al 1994;Maravilla et al 1998;Willms et al 2003;Willms et al 2004). …”
Section: Introductionmentioning
confidence: 99%